Educational Infrastructure in Rural India: A Compairitive Study of Gujarat and Rajasthan - Tanwar, Nirmal (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The paper aims to compare the education infrastructure in rural areas of Gujarat and Rajasthan. Both the states are rich in their cultural heritage, have semi-arid and desert conditions on their western edge and presence of Aravali mountain range. But providing educational infrastructure to remote areas in such physiographic condition is one challenge in itself and government policies play important role in the development of such regions. The results show poor condition in terms of infrastructure in the arid regions of both the states but some unique patterns have also emerged like coming of large number of private schools in school education in rural Rajasthan and greator number of male teachers as compared to female teachers. In comparison of infrastructure of rural schools Rajasthan is relatively better than rural schools of Gujarat.